Rhodium-catalyzed mild and selective C–H allylation of indolines and indoles with 4-vinyl-1, 3-dioxolan-2-one: facile access to indolic scaffolds with an allylic alcohol moiety. Issue 16 (22nd April 2015) - Sharma, Satyasheel; Shin, Youngmi; Mishra, Neeraj Kumar; Park, Jihye; Han, Sangil; Jeong, Taejoo; Oh, Yongguk; Lee, Youngil; Choi, Miji; Kim, In Su
Abstract: The rhodium(III)-catalyzed selective C–H allylations of indolines and indoles with 4-vinyl-1, 3-dioxolan-2-one at room temperature are described. These transformations provide the direct and efficient formation of indolic scaffolds containing an allylic alcohol group. Graphical abstract: